DETECTION SYSTEM OF OPTICAL LIGHTING HAZARDS TO RECEIVE THE RAYLEIGH HOLIDAYS COMPARED TO THE CONVENTIONAL SYSTEM - Suparno Suparno (Jurnal Penelitian Saintek, 2002)
mode fibre   optics  of 4.6pm  diameter  and  a quarter  pitch rens has been coupled by the use of SF connector  and stainless housing   to  produce   a  very  reliable   light   transducer.   The ltIII'SdulCeirs capable of transmitting  light thousands  times compared of using fibre  optics only. Besides  its ability  in transmittingit has  some  other  advantages  such  as  small  dimension   and relatively cheap cost of production.   The reliability  of the transducer ill transmitting  light was tested to observe scattered  light from  very JlnQIIparticles  of toluene known as Rayleigh scattering.